ADRENOCORTICAL CARCINOMA PRESENTING AS MALIGNANT HYPERTENSION WITH INTRACRANIAL BLEED - S, Rengasamy; SH, Nga; J, Nachiapan; A, Rivai; P, Vasanthan; YL, Lee (Journal of the ASEAN Federation of Endocrine Societies, 2019)
INTRODUCTION Adrenocortical carcinomas are rare tumours with a bimodal distribution, peaking at the age of less than 5 years and also around the 5th decade. In children, virilisation is the most common presentation while Cushing’s syndrome and hyperaldosteronism are less frequent. CASE We present a 6-month-old girl of Bangladeshi descent who presented at the age of 2 months old with status epilepticus following a trivial fall. She sustained a left intraventricular bleed with right front parietotemporal subarachnoid bleed. She underwent a right ventriculoperitoneal shunt insertion for obstructive hydrocephalus. Post operatively, she was noted to have recalcitrant hypertension with poor response to three antihypertensive therapy i.e. oral nifedipine, prazosin and captopril. During her hospitalisation, she developed rapid weight gain with development of facial acne and increasing facial, pubic and axillary hair. Hormonal investigations revealed elevated testosterone of 52.05 nmol/L, elevated DHEA of >27.1 µmol/L and elevated 17 hydroxyprogesterone of >60.6 nmol/L. Her morning (8am) cortisol was 1494 nmol/L while 12 midnight cortisol was 1493 nmol/L. A CT abdomen revealed a large right suprarenal mass measuring 5.5 cm x 6.4 cm x 6.6 cm. The tumour (9 cm x 8 cm) was removed completely at five months old, however intraoperatively it was noted to have capsular breach and tumour spillage. Histopathological examination confirmed the diagnosis of high-grade adrenocortical carcinoma. A repeat CT abdomen done two weeks post-operative, unfortunately revealed tumour recurrence measuring 3.9 cm x 4.5 cm x 4.8 cm at the subhepatic region. Hence chemotherapy (Cisplatin/ Etoposide/Doxorubicin) was initiated with addition of Mitotane. Postoperatively, her hypertension is gradually resolving within six weeks after surgery. CONCLUSION Invasive adenocarcinoma carries a poor prognosis. Early evaluation for this condition is vital in the presence of hypertension and virilisation in young children.